Market Power and Global Public Goods - Sebastian G. Kessing (Center for Economic Studies and ifo Institute (CESifo), 2023)
A global monopoly supplier country of necessary inputs for the provision of global public goods has an incentive to subsidize these exports. The strategic interdependence in the global public good context reverses the "large country" incentives to manipulate the terms-of-trade. It is optimal for a monopoly supplier country to deliberately worsen its terms of trade. The existence of a global monopoly supplier increases global public good supply relative to a competitive setting. Import-dependent countries may also benefit from a monopoly supplier. While they are strategically exploited to increase their contributions to the global public good, they do so at lower costs, and they benefit from increased contributions by the other importer countries.
Keywords: H41; D60; Q54; 330; global public goods; market power; climate policy; terms-of-trade; Inflation Reduction Act; Net Zero Industry Act